General sailing chart of the North West Coast of America from San Francisco to Bering Sea (U.S. Coast and Geodetic Survey, 1911)
Depths shown by soundings and isolines.; "April 1911."; "Corrections to . 1910."; "Compiled from United States, British and Russian authorities.; "Date of first publication 1892."; "Soundings in fathoms."; "Sailing chart S" -- upper left margin.; "Electrotype copy no. 3 C&GS" -- upper right margin. 1:3,600,000